2012
DOI: 10.1016/j.jmii.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Lethal toxic encephalopathy due to childhood shigellosis or Ekiri syndrome

Abstract: Lethal toxic encephalopathy due to shigellosis or Ekiri syndrome is a rare complication of shigellosis with a high fatality rate. Data are very limited on factors that can predict this encephalopathy, so we evaluated clinical and laboratory characteristics for these patients. In this study children with extreme toxicity and convulsions followed by rapid neurological deterioration resulting in brain edema and fatal outcome without sepsis and severe dehydration were selected as having lethal toxic encephalopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Shigella serogroups associated were S. flexneri , S. sonnei and S. dysenteriae (Agha and Goldberg ; Pourakbari et al . ).…”
Section: Extraintestinal Complications Of Shigella Serotypesmentioning
confidence: 97%
See 1 more Smart Citation
“…Shigella serogroups associated were S. flexneri , S. sonnei and S. dysenteriae (Agha and Goldberg ; Pourakbari et al . ).…”
Section: Extraintestinal Complications Of Shigella Serotypesmentioning
confidence: 97%
“…Neurologic recovery is often attainable, even though a fatal form of encephalopathy called Ekiri syndrome may occur in certain cases. Shigella serogroups associated were S. flexneri, S. sonnei and S. dysenteriae (Agha and Goldberg 2008; Pourakbari et al 2012).…”
Section: Neurological Complicationsmentioning
confidence: 99%
“…Encephalopathy is usually reversible, but sometimes it can be fulminate and fatal [ 11 ]. A lethal form of encephalopathy known as Ekiri syndrome (in Japanese ‘epidemic dysentery’) is characterized by rapidly developing seizure and coma with only mild colitis [ 12 , 13 ]. Although, neurological abnormalities and other extra intestinal manifestations are more common in children with Shigella dysentery type 1 infection, all four species of Shigella ( S .…”
Section: Introductionmentioning
confidence: 99%
“…7 A more recent study found 5 cases of lethal encephalopathy among 1295 children (0.4%) presented to the hospital with shigellosis. 6 However, it is unknown whether the Ekiri syndrome is the same as more recently reports on lethal toxic encephalopathy in children. It is possible that the high death rate among these Japanese children with Shigella enteric infection was a result of the standard of living in those times.…”
Section: Discussionmentioning
confidence: 94%
“… 4 5 All the known Shigella spp ( Shigella sonnei , Shigella flexneri , Shigella dysenteriae and Shigella boydii ) can cause this complication, with a prevalence of 12%–45% in children. 6 A lethal toxic encephalopathy with rapid onset of neurological abnormalities and only a mild colitis is known as the Ekiri syndrome. 7…”
Section: Introductionmentioning
confidence: 99%